2021
DOI: 10.1039/d0ta12425g
|View full text |Cite
|
Sign up to set email alerts
|

Side-chain-extended conjugation: a strategy for improving the photocatalytic hydrogen production performance of a linear conjugated polymer

Abstract: A side-chain-extended conjugation strategy is demonstrated here to improve photocatalytic performance of a linear conjugated polymer for hydrogen production from water. For it, polymer P0, P1, and P2 were designed...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
34
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 49 publications
(34 citation statements)
references
References 62 publications
0
34
0
Order By: Relevance
“…The high HER of 33.07 mmol h −1 g −1 for the bare PyTP-2 under visible light outperforms that of most previously reported organic photocatalysts (Table S1). For example, the triazine-based polymer of triazine-Th-CPP exhibited an HER of 4.43 mmol h −1 g −1 under visible-light irradiation [43], the D-A conjugated polymer of BTT-CPP showed an HER of 12.63 mmol h −1 g −1 under visible light [40], the sulfone-based conjugated copolymer of PS-5 gave an HER of 7.5 mmol h −1 g −1 under visible light illumination [48], and the linear conjugated polymer P2 showed an HER of 10.85 mmol h −1 g −1 [20]. Moreover, a direct comparison of PyTP-2 with the counterpart of CP1 produced from pyrene and bithiophene demonstrates that PyTP-2 shows a much higher HER (33.07 mmol h −1 g −1 ) than CP1 (15.97 mmol h −1 g −1 ) under visible light illumination [7].…”
Section: Articles Science China Materialsmentioning
confidence: 99%
See 1 more Smart Citation
“…The high HER of 33.07 mmol h −1 g −1 for the bare PyTP-2 under visible light outperforms that of most previously reported organic photocatalysts (Table S1). For example, the triazine-based polymer of triazine-Th-CPP exhibited an HER of 4.43 mmol h −1 g −1 under visible-light irradiation [43], the D-A conjugated polymer of BTT-CPP showed an HER of 12.63 mmol h −1 g −1 under visible light [40], the sulfone-based conjugated copolymer of PS-5 gave an HER of 7.5 mmol h −1 g −1 under visible light illumination [48], and the linear conjugated polymer P2 showed an HER of 10.85 mmol h −1 g −1 [20]. Moreover, a direct comparison of PyTP-2 with the counterpart of CP1 produced from pyrene and bithiophene demonstrates that PyTP-2 shows a much higher HER (33.07 mmol h −1 g −1 ) than CP1 (15.97 mmol h −1 g −1 ) under visible light illumination [7].…”
Section: Articles Science China Materialsmentioning
confidence: 99%
“…Compared with inorganic semiconductor materials, organic semiconductor materials recently attract more interest because of their flexible structural design, diverse synthetic strategies and tunable electronic properties [9][10][11][12][13][14]. To date, the developed organic polymer photocatalysts mainly include graphitic carbon nitrides [15][16][17], linear conjugated polymers [18][19][20][21][22], conjugated microporous polymers (CMPs) [23][24][25][26][27], crystalline covalent organic frameworks (COFs) [28][29][30][31] and covalent triazine-based frameworks (CTFs) [32][33][34][35].…”
Section: Introductionmentioning
confidence: 99%
“…It has been demonstrated that reducing the bandgap or enhancing the conjugation degree of the building blocks is an effective strategy to broaden the light absorption range and increase the photocatalytic performance of BTDO containing polymer photocatalysts under visible light irradiation. [ 24,29–32 ] For instance, Cooper and co‐workers extended the conjugation of BTDO unit by synthesizing 3,9‐diamino‐benzo[1,2‐b:4,5‐b′]bis[1]benzothiophenesulfone, which efficiently broadened the light absorption range and enhanced the hydrogen evolution rate (HER) to 10.1 mmol h –1 g –1 for the resulting polymer under visible light. [ 31 ] We replaced the benzene ring in BTDO unit by thiophene to develop an electron acceptor unit of dithieno[3,2‐b:2′,3′‐d]thiophene‐S,S‐dioxide with narrow bandgap, which enabled the resulting D–A CMP photocatalysts to exhibit a light absorption range up to 700 nm with a high HER of 16.3 mmol h –1 g –1 as irradiated by visible light.…”
Section: Introductionmentioning
confidence: 99%
“…[ 22 ] Li and co‐workers reported that the introduction of thiophene side chain on the electron donating unit could increase the conjugation of the BTDO‐containing polymers and an HER of 10.85 mmol h –1 g –1 was obtained, which is 160 times higher than that of its counterpart polymer without thiophene side chain under full‐arc light range (0.068 mmol h –1 g –1 ). [ 32 ] Although developing novel monomers with high conjugation degree or narrow bandgap can enhance the photocatalytic performance of BTDO containing polymer photocatalysts, the synthetic process of these novel building blocks might increase the cost and complexity for preparing the resulting polymers, which could limit the real‐world application. Notably, there is still a huge gap between the photocatalytic performance of the reported BTDO‐containing polymer photocatalysts and the requirement in practical application.…”
Section: Introductionmentioning
confidence: 99%
“…Remarkable progress in photo‐catalytic performance has been achieved, with the hydrogen evolution rate (HER) surpassing 10 000 µmol g −1 h −1 under visible irradiation. [ 22,27,38–40 ] For example, McCulloch et al. reported the organic photo‐catalyst based on heterojunction nanoparticles, which displayed an unprecedentedly high HER of over 60 000 µmol g −1 h −1 .…”
Section: Introductionmentioning
confidence: 99%